Rodinné vinařství Plchut Mutěnice - Mahdalík, Jakub (Vysoké učení technické v Brně. Fakulta stavební, 2023)
ZADÁNÍ BAKALÁŘSKÉ PRÁCE JE NÁVRH NOVOSTAVBY RODINNÉHO VINAŘSTVÍ PLCHUT V MUTĚNICÍCH, V JIHOMORAVSKÉ VINAŘSKÉ OBLASTI. BAKALÁŘSKÁ PRÁCE VYCHÁZÍ ZE STUDIE, KTERÁ BYLA VYPRACOVÁNA V RÁMCI PŘEDMĚTU AG032. CÍLEM ARCHITEKTONICKÉ STUDIE BYLO PROVÉST NÁVRH VINAŘSTVÍ, KTERÝ ZAHRNOVAL ADMINISTTATIVNÍ OBJEKT A OBJEKT VÝROBY. CÍLEM BAKALŘÁSKÉ PRÁCE JE ROZPRACOVAT TUHLE STUDII A VYPRACOVAT PROJEKTOVOU DOKUMENTACI VE STUPNI PRO POVOLENÍ STAVBY A PROVÁDĚNÍ STAVBY. PŘIDĚLENÝ POZEMEK SE NACHÁZÍ NA ZAPADNÍM OKRAJI OBCE MUTĚNICE V JIHOMORAVSKÉM KRAJI. NÁVRH JE ROZDĚLEN NA DVA SAMOSTATNĚ STOJÍCÍ OBJEKTY. JEDEN Z OBJEKTŮ JE VÝROBNÍ HALA PRO VÝROBU VÍN. VE DRUHÉM OBJEKTU SE NACHÁZÍ ADMINISTRATIVA A UBYTOVÁNÍ. NAVRŽENÝ OBJEKT RESPEKTUJE VÝRAZ OKOLNÍ KRAJINY A JE NAVRŽEN VE VZTAHU S ARCHITEKTONICKÝM VÝRAZEM OBCE. OBJEKT VÝROBNÍ HALY JE JEDNOPODLAŽNÍ. NACHÁZÍ SE ZDE VÝROBA A SKLADY. DVŮR NABÍZÍ MÍSTO PRO PARKOVÁNÍ, MANIPULAČNÍ PROSTOR A PROSTOR PRO PLNÍCÍ LINKU. DO OBJEKTU JSOU NAVRŽENY 3 VJEZDY. OBJEKT ADMINISTRATIVY JE PŘÍZEMNÍ S JEDNÍM PODZEMNÍM PODLAŽÍM. PRVNÍ NADZEMNÍ PODLAŽÍ SLOUŽÍ K PREZENTACI A PRODEJI VÍN, K UBYTOVANÍ VE DVOU APARTMÁNECH A K ADMINISTRATIVĚ. PODZEMNÍ PODLAŽÍ SLOUŽÍ K ARCHIVACI A DEGUSTACI VÍN. ZÁROVEŇ SE ZDE NACHÁZÍ ZÁZEMÍ K PŘÍPRAVĚ MALÉHO OBČERSTVENÍ, TECHNICKÁ MÍSTNOST A TOALETY. NA POZEMEK JE NAVRŽEN JEDEN VJEZD PRO ZÁSOBOVÁNÍ. PRO NÁVŠTĚVNÍKY SLOUŽÍ PARKOVIŠTĚ A VSTUP NA JIHU POZEMKU. AREÁL JE NAVRŽEN BEZBARIÉROVĚ.

THE ASSIGNMENT OF THE BACHELOR'S THESIS IS THE DESIGN OF THE NEW BUILDING OF THE PLCHUT FAMILY WINERY IN MUTĚNICE, IN THE SOUTH MORAVIA WINE REGION. THE BACHELOR'S THESIS IS BASED ON THE STUDY WHICH WAS DEVELOPED WITHIN THE SUBJECT AG032. THE OBJECTIVE OF THE ARCHITECTURAL STUDY WAS TO IMPLEMENT THE DESIGN OF THE WINERY WHICH INCLUDED AN ADMINISTRATIVE FACILITY AND A PRODUCTION FACILITY. THE GOAL OF THE BACHELOR'S THESIS IS TO DEVELOP THIS STUDY AND DEVELOP PROJECT DOCUMENTATION AT THE STAGE FOR BUILDING PERMIT AND IMPLEMENTATION OF CONSTRUCTION. THE ALLOCATED LAND IS LOCATED ON THE WESTERN EDGE OF THE MUNICIPALITY OF MUTĚNICE IN THE SOUTH MORAVIAN REGION. THE DESIGN IS DIVIDED INTO TWO INDEPENDENT OBJECTS. ONE OF THE OBJECTS IS A PRODUCTION HALL FOR WINE PRODUCTION. ADMINISTRATION AND ACCOMMODATION ARE LOCATED IN THE SECOND BUILDING. THE DESIGNED OBJECT RESPECTS THE EXPRESSION OF THE SURROUNDING LANDSCAPE AND IS DESIGNED IN RELATION TO THE ARCHITECTURAL EXPRESSION OF THE VILLAGE. OBJECT OF THE PRODUCTION HALL IS ONE FLOOR. PRODUCTION AND WAREHOUSES ARE LOCATED HERE. THE YARD OFFERS A PLACE FOR PARKING, HANDLING AREA AND SPACE FOR A FILLING LINE. THERE ARE 3 ENTRANCES DESIGNED TO THE BUILDING OF PRODUCTION. THE ADMINISTRATION BUILDING IS GROUND FLOOR WITH ONE UNDERGROUND FLOOR. THE FIRST GROUND FLOOR IS USED FOR THE PRESENTATION AND SALE OF WINES, FOR ACCOMMODATION IN TWO APARTMENTS AND FOR ADMINISTRATION. THE UNDERGROUND FLOOR IS USED FOR THE ARCHIVING AND TASTING OF WINES. THERE ARE FACILITIES FOR THE PREPARATION OF SMALL REFRESHMENTS, A TECHNICAL ROOM AND TOILETS TOO. ONE SUPPLY ENTRANCE IS PROPOSED TO THE LOT. THE PARKING LOT AND THE ENTRANCE TO THE SOUTH OF THE PROPERTY SERVE FOR VISITORS. THE AREA IS DESIGNED TO BE BARRIER-FREE.
Family winery Plchut Mutěnice
Keywords: VINAŘSTVÍ; VÍNO; TRADIČNÍ METODA; DEGUSTACE; OBČERSTVENÍ; PREZENTACE VÍN; SEDLOVÁ STŘECHA; ARCHITEKTURA; VÝROBA VÍN; VINICE; POROTHERM; UBYTOVÁNÍ; MUTĚNICE; NOVOSTAVBA; WINERY; WINE; TRADITIONAL METHOD; TASTING; REFRESHMENT; PRESENTATION OF WINES; SEDDLE ROOF; ARCHITECTURE; WINE PRODUCTION; VINEYARD; POROTHERM; ACCOMMODATIONS; MUTĚNICE; NEW CONSTRUCTION.